Os Corpos de Trabalhadores no Baixo Amazonas, em meados do século XIX: o caso da “Sedição” de Pinhel (1858) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This study seeks to contribute to an understanding of the complex world of labour in 19th century Amazonia by analysing the applicability of the legislation that established the Workers' Corps in the Province of Grão-Pará, specifically in the district of Santarém, in the Lower Amazon region, the main objective of the research. Through practices aligned with the conservative advance of the Second Reign and the affirmation of the newly built national state in the different regions of the Empire, the Workers' Corps were organised to carry out compulsory labour recruitment in an Amazon still shaken by the Cabanagem. This was one of the solutions devised to reorganise the world of work, marked by the coexistence of free, slave and compulsory forms of labour. Beyond the intentions of the legislation, the objective of observing its applicability will be sought by analysing the case treated by the authorities as the Pinhel Sedition. The methodology used was the qualitative analysis of a set of documentary sources: criminal cases from the judicial fund, provincial laws, reports from the presidents of the province of Pará and newspapers; in parallel with the dialogue with the bibliography focused on the social history of labour. Thus, through the case known as the Pinhel Sedition, the Company of Workers (or Workers' Corps) of Pinhel and Santarém was analysed. As a result, the way in which the subjects involved in the application of the legislation re-signified the law that instituted them was noted, revealing the spaces of agency and resistance that were undertaken by them.
Keywords: Segundo Reinado; Corpos de Trabalhadores; Grão-Pará; Mundo do Trabalho; CNPQ:: CIÊNCIAS HUMANAS